Recurrence of follicular dendritic cell sarcoma in tonsils after 7 years: a rare case report - Pawar, Pratiksha; Kangloo, Shubhanshi; Bihani, Ameya; Gupta, Kunal; Yadav, Soma (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2023)
Follicular dendritic cell sarcoma (FDCS) is a rare mesenchymal neoplasm. It arises from not only from lymph nodes but also from extra nodal tissues, either as acquired lymphoid tissue or as part of the organized constitutive lymphoid tissue. We here report this rare entity which developed again after 7 years post tonsillectomy in a 5-year old male patient. Patient underwent radical tonsillectomy and adjuvant treatment is awaited. Differential diagnosis includes large cell lymphoma, peripheral nerve sheath tumor, extracranial meningioma, malignant melanoma, metastatic carcinoma, ectopic thymoma, malignant fibrous histiocytoma, and interstitial reticulum cell sarcoma. Currently, the management of FDCS includes the therapeutic guidelines similar to that of high-grade soft tissue sarcomas that is complete surgical resection of the lesion with possibility of adjuvant radiotherapy and/or chemotherapy. The ideal combination of management of FDCS has yet to be defined.